Surviving in the city: higher apparent survival for urban birds but worse condition on noisy territories. Issue 9 (25th September 2018) - Phillips, Jennifer N.; Gentry, Katherine E.; Luther, David A.; Derryberry, Elizabeth P.
Abstract: Anthropogenic landscapes and soundscapes impose strong selective pressures on a number of species, which can manifest in changes in vocalizations, foraging strategies, predator vigilance, and reproductive success. However, few studies have examined survival rates, a major component of fitness, across urban landscapes and soundscapes. White‐crowned sparrows ( Zonotrichia leucophrys ) persist in both urban and rural landscapes and change their behavior in response to the soundscape. We color‐banded adult white‐crowned sparrows and collected noise levels on their territories in the urban San Francisco Bay Area and adjacent rural Point Reyes National Seashore in California. We collected mark‐encounter data on territorial males from 2014 to 2017. Using the Program MARK, we tested the effects of habitat (urban/rural) and territory noise level on annual survival rates and body condition. We predicted that survival and body condition would be lower in urban habitats and decrease with increasing background noise level on territories. We found that survival estimates vary according to year, and males in urban landscapes have higher survival. Noise levels best predict body condition, such that soundscape negatively correlates with male body condition. Taken together, the urban landscape and soundscape shape the survival and health of birds in and near cities.